(untitled) (International Journal on Stereo & Immersive Media, 2021)
Stereoscopy occupied a prominent place in amateur photography in the first third of the 20th century. Amateur photographers used it to record their excursions and trips, often in the landscape and monumental tradition of nineteenth-century tourist photography. Other themes were also added: leisure, family scenes, cultural concerns, etc. One example is the work of the Mallorcan doctor Jaume Escalas Real (1893-1979), who used stereoscopic and other techniques (1915-1975) to record landscapes, events, everyday life and travel. He was also a leading promoter of Mallorca’s tourist projection thanks to his graphic guides (begun in the 1930s). His photographic collection has been preserved with hundreds of positives and stereoscopic negatives, as well as his cameras and accessories.